1991
DOI: 10.1111/j.2517-6161.1991.tb01857.x
|View full text |Cite
|
Sign up to set email alerts
|

A Reliable Data-Based Bandwidth Selection Method for Kernel Density Estimation

Abstract: SUMMARY We present a new method for data‐based selection of the bandwidth in kernel density estimation which has excellent properties. It improves on a recent procedure of Park and Marron (which itself is a good method) in various ways. First, the new method has superior theoretical performance; second, it also has a computational advantage; third, the new method has reliably good performance for smooth densities in simulations, performance that is second to none in the existing literature. These methods are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
1,212
0
5

Year Published

1993
1993
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 1,803 publications
(1,278 citation statements)
references
References 7 publications
8
1,212
0
5
Order By: Relevance
“…4) are a consequence of these ad hoc modifications to this method made to take into account the lack of present-day volcanism in our study areas. In addition, the degree to which the data has been smoothed by the selected bandwidths-one for each data point-has been solved rather subjectively to be either twothirds of the Sheather and Jones (1991) automatically chosen bandwidth for data without measurement error or 1.25 times the standard deviation, whichever is the larger.…”
Section: Preliminary Data Analysismentioning
confidence: 99%
“…4) are a consequence of these ad hoc modifications to this method made to take into account the lack of present-day volcanism in our study areas. In addition, the degree to which the data has been smoothed by the selected bandwidths-one for each data point-has been solved rather subjectively to be either twothirds of the Sheather and Jones (1991) automatically chosen bandwidth for data without measurement error or 1.25 times the standard deviation, whichever is the larger.…”
Section: Preliminary Data Analysismentioning
confidence: 99%
“…As a first approximation, one can clearly use a procedure which ignores boundary considerations, and this we did, using Sheather and Jones' (1991) method, in Fig. 7.…”
Section: Closing Remarksmentioning
confidence: 99%
“…Sheather (1983) suggested another approach but later showed that bias is a concern and derived a method for getting better results (Sheather 1986). More recently, Sheather and Jones (1991) investigated other methods aimed at minimizing a kernel-based estimate of MISE. But perhaps a more basic issue is whether plug-in methods, such as those just cited, should be used over what are called classic methods, which include cross-validation, Mallow's C p criterion, and Akaike's information criterion (AIC).…”
Section: Density Estimationmentioning
confidence: 99%